The Belt and Road Initiative Reshaping Economic Geography in Central Asia? - Bird, Julia Helen (World Bank E-Library Archive, 2019)
This paper develops a computable spatial equilibrium model of Central Asia and uses it to analyze the possible effects of the Belt Road Initiative on the economy of the region. The model captures international and subnational economic units and their connectivity to each other and the rest of the world. Aggregate real income gains from the Belt Road Initiative range from less than 2 percent of regional income if adjustment mechanisms take the form of conventional Armington and monopolistic competition, to around 3 percent if there are localization economies of scale and labor mobility. In the latter case, there are sizeable geographical variations in impact, with some areas developing clusters of economic activity with income increases of as much as 12 percent and a doubling of local populations, while other areas stagnate or even decline